Welding Defects Analysis with Various Alloys Using TIG and MIG Welding Process - Miah, Md Abdul Hannan; Abedin, Mohammad Zoynal; Hossain, Md. Selim; Ali, Md. Ashraf; Rana, Md. Masud; Islam, Samsul; Ahsan, Zahid; Islam, Shariful (Transactions on Engineering and Computing Sciences, 2023)
This paper aims to analyze the process of tungsten inert gas and metal inert gas welding and the defects of welding. Metal inert gas and Tungsten inert gas welding are the most popular gas-shielded arc welding processes used in many industrial fields. MIG welding is more highly efficient than TIG welding. This research has focused on welding defects with various types of welding joints for various metal alloys by using tungsten inert gas and metal inert gas welding processes. In this work, mechanical properties such as yield stress, elastic stress, and breaking stress have also been found for both TIG and MIG welding processes.